Tidal Flood Mapping with a Simple Bathtub Model in Sungai Kakap District, Indonesia - Andin Maulana Yusuf Farhan; Joko Sampurno; Irfana Diah Faryuni (Universitas Lambung Mangkurat, 2025)
Sungai Kakap District, located in Kubu Raya Regency, West Kalimantan, is a low-lying coastal region highly exposed to tidal dynamics, making it susceptible to recurrent tidal flooding (rob). Accurately mapping spatially explicit flood extents is a vital foundation for vulnerability assessment, disaster preparedness, and mitigation planning. This study aims to map the tidal flood extent during a significant event in December 2024 in Sungai Kakap District using a static inundation approach known as the Simple Bathtub Model. The research methodology integrated historical water level data from the BMKG Pontianak Maritime Station with a Digital Elevation Model (DEM) derived from SRTM data. By setting a maximum water level threshold of 1.8 meters based on peak tidal records, the inundated areas were identified and mapped using the Google Earth Engine (GEE) platform. To ensure reliability, the resulting flood map was validated against field observations using a confusion matrix. Validation results demonstrated an overall accuracy (OA) of 0.74 and a Kappa coefficient of 0.43, indicating that the model provides a moderate but acceptable representation of flood patterns in low-lying deltaic plains. Spatial impact analysis revealed significant socioeconomic consequences: the flood inundated approximately 150,000 meters of the road network, submerged between 900 and 1,000 buildings, and affected an estimated 16,000 to 17,000 residents. These findings highlight the high vulnerability of coastal communities in West Kalimantan and demonstrate that the Simple Bathtub Model is a practical and effective tool for supporting local governments in developing data-driven mitigation strategies and enhancing long-term coastal resilience.